2022
DOI: 10.1159/000521729
|View full text |Cite
|
Sign up to set email alerts
|

Obesity in Older Adults and Associations with Cardiovascular Structure and Function

Abstract: Introduction: Body mass index (BMI), despite being widely used as a marker of obesity, fails to fully capture cardiovascular risks as it is an insufficient biomarker of abdominal adiposity, unlike waist circumference (WC). We aim to characterize associations between BMI and WC with cardiovascular structure and function in older adults. Methods: Among an observational cohort study of community older adults, transthoracic echocardiography determined cardiovascular structure and function, while aerobic capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Notwithstanding the relative degree of involvement by adipose tissues or skeletal muscles, there is now greater awareness and scientific acknowledgment that there are close relationships between body composition and heart structure and function. This is in line with the opinion that the observed degenerative bodily changes in older adults is the result of the complex interplay between body composition, the cardiovascular system and aging process ( 79 ), far more granular than the body mass index metric ( 78 ).…”
Section: Cardio-sarcopenia—next Stepssupporting
confidence: 88%
See 1 more Smart Citation
“…Notwithstanding the relative degree of involvement by adipose tissues or skeletal muscles, there is now greater awareness and scientific acknowledgment that there are close relationships between body composition and heart structure and function. This is in line with the opinion that the observed degenerative bodily changes in older adults is the result of the complex interplay between body composition, the cardiovascular system and aging process ( 79 ), far more granular than the body mass index metric ( 78 ).…”
Section: Cardio-sarcopenia—next Stepssupporting
confidence: 88%
“…Firstly, there is a need for mechanistic understanding of the cross-talk between the various components of body composition and the cardiac muscles. Earlier research has revolved around obesity and its association with cardiovascular structure and function ( 77 , 78 ). With emerging interest in skeletal muscles, sarcopenia enters the equation for the consideration of LVM.…”
Section: Cardio-sarcopenia—next Stepsmentioning
confidence: 99%
“…Physical inactivity has been associated with a higher prevalence of overweight/obesity, in addition to increasing the risk of comorbidities in older people, which may affect muscle strength [ 4 , 35 ]. It has been observed that high levels of adiposity can affect agonist muscle activation, which can lead to functional limitations during old age [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sinus rhythm status was ascertained by a resting electrocardiogram. Waist circumference was obtained 2.5 cm above the umbilicus [ 23 ].…”
Section: Methodsmentioning
confidence: 99%